An African History of Africa from the dawn of humanity to independence - Badawi, Zeinab (London Penguin Random House, 2024)
For too long, Africa?s history has been dominated by western narratives of slavery and colonialism, or simply ignored. Now, Zeinab Badawi sets the record straight.
Includes index
Keywords: Africa